ASSOCIATION BETWEEN SMOKING BEHAVIOUR AND GLYCOHEMOGLOBINE LEVELS AMONG ADULT JAVANESE INDONESIAN SMOKERS - Christine Patramurti; Fenty Fenty (Sanata Dharma University, 2020)
Nicotine, the active compound in cigarettes, can cause impaired glucose metabolism byincreasing insulin resistance as well as decreasing insulin secretion in ? cell pancreas. Thiscondition can increase the risk of type 2 diabetes in human. This study aims to evaluate the effectof smoking behaviour, determined by Cigarette per Day (CPD) and smoking duration, onglychohemoglobine (HbA1c) levels of Javanese Indonesian smokers. 30 smokers were studiedconsisting of 7 smokers with 10 CPD, 19 smokers with 11-20 CPD and 4 smokers with 21-30CPD. They had been smoking for more than 10 years. The whole blood sample was used toexamine the HbA1c levels. The HbA1c levels were tested at Bethesda Hospital's cliniclaboratories using Architect 600 instrument. The results showed that CPD and smoking durationsignificantly influenced HbA1c, in which F count was F table (370.541 3.354) withsignificance 0.05 (2.35. 10-20 0.05) and multiple correlation coefficient (R) of 0.982.Therefore, based on this research finding, it was concluded that longer smoking duration andhigher CPD caused higher smokers HbA1c level.